HUBUNGAN DUKUNGAN PARA ANGGOTA KOMUNITAS DENGAN RESILIENSI IBU DOWN SYNDROME - Badriatuzzahroh Nur Siti; Endang Supraptiningsih; Stephani Raihana Hamdan (Jurnal Psikologi TALENTA, 2018)
Researchers found a link between members community support with maternal resilience. Mother who has Down syndrome children in POTADS Bandung is able to show resilience in the face of a stressful situation in the process of raising a child's down syndrome due to the help of the community POTADS. The purpose of this study is to obtain empirical data on the corelation between community members' support and maternal resilience in mothers with Down syndrome children in POTADS Bandung. The method used is correlational. The study involved 50 mothers. The measuring instrument used is a questionnaire developed from the concept Social support from Sarafino & Smith (2011) and Resilience Bernard (2004). The result of data processing shows the value of rs = 0,322 with ρ = 0,023, with aspect of information support that is equal to rs = 0,331, so it can be concluded that there is positive correlation with low degree of correlation between support of community member with resilience at mother having child down syndrome in POTADS Bandung and the most supportive aspects are the information support that can increased the mother resilience.